Indonesia in Ghadan Ansā and Al-Jāwiyyah: Saudi Critical Perspectives on Two Contemporary Saudi Novels - Mahdi, Rijal; Suhane, Shuhaida Hanim Mohamad; Elawadi, Elsayed Mohamed Salem Salem (Borneo Journal of Language and Education, 2026)
Scholarly discussion of Indonesia’s representation in contemporary Arabic literature, particularly in Saudi novels, remains limited, despite the important ways these works portray Indonesia’s cultural, social, and spatial dimensions within modern Saudi literary imagination. This study aims to analyze the representation of Indonesia in two Saudi novels, Ghadan Ansā by Amal Shatta and Al-Jāwiyyah by Muhammad Muhsin al-Ghamidi, while also examining the literary significance of these works and the position of their authors in contemporary Saudi prose fiction. The study employs a descriptive-analytical method within a comparative framework. Primary data are drawn from the two novels, while secondary data consist of relevant academic studies and literary criticism. The analysis is conducted through close textual reading and biographical examination of the authors. The findings show that Amal Shatta constructs a narrative in which time, rather than space, serves as the principal driving force, reflecting a strong humanistic vision in portraying the intensity and harshness of temporal experience. In contrast, Muhammad al-Ghamidi is distinguished by his layered and complex use of symbolism, especially in the construction of titles and narrative structure, which invites reflective and interpretive reading. The study concludes that both novels contribute to the construction of Indonesia as the “near other” in Saudi cultural imagination and enrich cross-cultural representation studies within comparative literature.